2016
DOI: 10.1093/hmg/ddw273
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of Klippel-Trenaunay syndrome geneAggf1inhibits developmental and pathological angiogenesis by inactivating PI3K and AKT and disrupts vascular integrity by activating VE-cadherin

Abstract: Aggf1 is the first gene identified for Klippel-Trenaunay syndrome (KTS), and encodes an angiogenic factor. However, the in vivo roles of Aggf1 are incompletely defined. Here we demonstrate that Aggf1 is essential for both physiological angiogenesis and pathological tumour angiogenesis in vivo. Two lines of Aggf1 knockout (KO) mice showed a particularly severe phenotype as no homozygous embryos were observed and heterozygous mice also showed embryonic lethality (haploinsufficient lethality) observed only for Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(114 citation statements)
references
References 47 publications
2
110
1
1
Order By: Relevance
“…AGGF1 is required for specific differentiation of veins and development of intersegmental vessels during zebrafish embryogenesis,35 which was confirmed by Kashiwada et al 36. Our recent studies using AGGF1 +/− knockout (KO) mice showed that AGGF1 is essential for early embryogenesis and vascular development, and blocks vascular permeability 37. We have found that AGGF1 is an important signaling factor that can induce autophagy by activating JNK,33 regulate angiogenesis and vascular development by activating PI3K, AKT, GSK3β, and S6K and inhibiting ERK1/2 (also reported by Hu et al38), and maintain vascular integrity by inhibiting VE‐cadherin phosphorylation 35, 37.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…AGGF1 is required for specific differentiation of veins and development of intersegmental vessels during zebrafish embryogenesis,35 which was confirmed by Kashiwada et al 36. Our recent studies using AGGF1 +/− knockout (KO) mice showed that AGGF1 is essential for early embryogenesis and vascular development, and blocks vascular permeability 37. We have found that AGGF1 is an important signaling factor that can induce autophagy by activating JNK,33 regulate angiogenesis and vascular development by activating PI3K, AKT, GSK3β, and S6K and inhibiting ERK1/2 (also reported by Hu et al38), and maintain vascular integrity by inhibiting VE‐cadherin phosphorylation 35, 37.…”
Section: Introductionmentioning
confidence: 70%
“…Based on our extensive analyses of reported data in the literature and our preliminary data, we concluded that the AGGF1‐mediated ERK signaling pathway is the most relevant and logical signaling pathway for AGGF1 in VSMCs. Therefore, our research plans focus on the AGGF1‐ERK signaling, which has been well documented in the literature 37, 38. It should be interesting to explore other AGGF1‐mediated signaling pathways, such as AKT, JNK, and other pathways, in VSMCs functions and neointimal formation in the future.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations